Hydrothermal parameters enhancement of a DTHEX with simultaneous V-cut twisted tape turbulator and air/CuO-water flow usage - Zhang Jie; Salina Binti Muhamad; Azher M. Abed; Ahmed Deifalla; S.P. Ghoushchi; Izyani Mat Rusni (Case Studies in Thermal Engineering, 2023)
Numerous studies have been conducted to assess the effect of using a V-cut twisted tape turbulator, bubble injection method, and CuO-water nanofluid as a working fluid separately on the hydrothermal parameters. For the first time, the current study aimed to comprehensively evaluate the effect of the simultaneous use of these three methods on the effectiveness, friction factor, and thermal performance enhancement factor of a double-tube heat exchanger. Experiments were conducted with Reynolds numbers ranging from 7200 to 14500. Air was injected into the working fluid with a flow rate of 2 to 6 L/min. A turbulator with different geometry was also inserted in the inner tube. The results showed that using the methods separately increased effectiveness by up to 81%, while their simultaneous use increased the effectiveness to 2.36 times that of the plain tube. The friction factor in the presence of these three methods is up to 1.11 to 14.36 times that of a plain tube heat exchanger, respectively. In addition, the results showed that combining these three methods significantly affected thermal performance enhancement factor (TEF), increasing it to 1.46.